Prognosis and clinical outcome of papilloma neoplasm of the breast: An observational study - Puttiporn Naowaset (Cancer Treatment and Research Communications)
Objective: due to rarity of this subtype, the aim of this study was to investigate the clinicopathological features, treatment, and prognosis of papillary carcinoma of the breast. Materials and methods: The histopathologic reports of all papillary breast lesion from January 1, 2010, to January 31, 2020, at Ramathibodi hospital were retrieved, comprising a total of 544 reports. Of the 133 (24.44 %) histopathologically proved papillary lesions, 411 (75.55 %) lesions were excluded from this study due to mixed histopathologic type. The clinical characteristics including age, menopausal status, clinical presentation, the presence of mass, presence of suspicious calcification were recorded. Diagnostic and tumor characteristics including immunohistochemistry, Nottingham grade of tumor, pathological stage were recorded. Local and systemic treatment including type of surgery, chemotherapy, radiation therapy, anti-hormonal therapy and targeted therapy were recorded. Prognosis including overall and disease-free survival were recorded. Results: Of 133 papillary lesions, 47 lesions were invasive solid papillary carcinoma, 7 lesions were invasive encapsulated papillary carcinoma, 31 lesions were solid papillary carcinoma, 27 lesions were encapsulated papillary carcinoma, 16 lesions were invasive papillary carcinoma, and 5 lesions were intraductal papillary carcinoma. The mean follow-up period was 64 months, during which we identified 6 cases of recurrence. Additionally, non-cancer-related deaths were observed in 2 patients. There was no significant difference in disease free survival (DFS) among all types, with a rate of 95.49 %. Similarly, overall survival (OS) showed no significant difference, with a rate of 98.5 % Conclusion: Papillary carcinoma is a rare variant of breast tumor. All papillary carcinomas, including the invasive types, exhibit an excellent prognosis. It is suggested that invasive papillary carcinoma should be considered a subtype with a favorable prognosis, allowing for minimization of treatment accordingly.